РЕФОРМЫ И ИХ ПОСЛЕДСТВИЯ В АГРАРНОМ СЕКТОРЕ КАРАКАЛПАКСТАНА В 1960-1970-е ГОДЫ - Шамшетдинова, Д.И. (SCIENCE and SOCIETY, 2025)
The article examines the agrarian transformations in Karakalpakstan during the 1960-1970. It analyzes the consolidation of collective farms, the establishment of state farms, the development of cotton growing and rice cultivation, as well as the impact of mechanization and chemicalization in agriculture. While highlighting improvements in labor productivity and crop yields, the study also reveals negative social and environmental consequences of cotton monoculture and the excessive use of chemical substances.